Suhu dan Masa Simpan Benih Memengaruhi Viabilitas Benih Mahoni (Swietenia macrophylla King.): Temperature and Seed Storage Period Affect Mahogany Seed Viability (Swietenia macrophyllaKing.) - Kartiko, Wilda Ulinnuha; Tata, Made Hesti Lestari; Triadiati, Triadiati (Jurnal Sumberdaya Hayati, 2024)
Swietenia macrophylla or big-leaf mahogany is an exotic species from Central and South America. This tree has various benefits, so it’s used as an industrial plantation forest and afforestation in Indonesia. However, seed storage of mahogany is a major problem in cultivation, because it can reduce seed viability. The storability of seeds is influenced by seed and environmental conditions. Therefore, this study aimed to examine the effect of temperature and storage time on the viability of S. macrophylla seeds and to calculate the Seedling Quality Index (SQI). The experiment was carried out using a factorial Randomized Block Design (RBD) with 2 factors. The first factor was consisted of four levels of temperature treatment, namely room temperature (24), 4, 0, and -20°C. The second factor was the storage period treatment which consisted of 4 levels, namely 1 up to 4 weeks, with 1-week intervals. The results showed that the interaction between temperature and storage time affected mahogany leaves, primary and secondary roots, root/shoot ratio, and total wet weight of S. macrophylla seedlings. Mahogany seeds that were stored at room temperature for 1 week resulted in the highest seed viability, with SQI of 0.03-0.04.